1988
DOI: 10.1139/b88-288
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia, glutamine, and asparagine: a carbon–nitrogen interface

Abstract: In plants, the primary input of nitrogen (obtained from the soil or from symbiotic dinitrogen fixation) occurs through the assimilation of ammonia into organic form. Synthesis of glutamine (via glutamine synthetase) is the major, and possibly exclusive, route for this process, and there is little evidence for the participation of glutamate dehydrogenase. A variety of reactions distribute glutamine nitrogen to other compounds, including transfer to amino nitrogen through glutamate synthase. In many plants aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
7

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(90 citation statements)
references
References 46 publications
2
81
0
7
Order By: Relevance
“…The L-asparaginase (E.C.3.5.l.l) an aminohydrolasecatalyses effect involved asparagine hydrolysis to yield L-aspartate and ammonia [2,14,17]. L-glutamine to L-glutamate as well as L-asparagine transamination [17,18]. Several investigators [8,14,19] reported an internal and external L-aspargenases were biochemically and genetically distinct in different plants.…”
Section: Introductionmentioning
confidence: 99%
“…The L-asparaginase (E.C.3.5.l.l) an aminohydrolasecatalyses effect involved asparagine hydrolysis to yield L-aspartate and ammonia [2,14,17]. L-glutamine to L-glutamate as well as L-asparagine transamination [17,18]. Several investigators [8,14,19] reported an internal and external L-aspargenases were biochemically and genetically distinct in different plants.…”
Section: Introductionmentioning
confidence: 99%
“…GS 1 plays a major role in the assimilation of ammonia derived from N 2 fixation in the nodules and also has an important role in the remobilization of nitrogen during senescence, bacterial infection, herbicide treatment and water stress (Bauer et al 1997;Pérez-García et al 1998;Brugiere et al 2000;Masclaux et al 2000). GS 1 is the main isoform involved in the assimilation of external ammonia (Sukanya et al 1994) and the ammonia derived from other sources of nitrogen, like the synthesis of secondary metabolites and the recycling of nitrogen from protein catabolism (Joy 1988). Root GS 1 may also have a role in the assimilation of the ammonia derived from nitrate reduction in the roots (Lancien et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to most plants, the free amino acid pool of both male and female saps (Table 3) was dominated by glutamine, asparagine (Fischer et al, 1998), and arginine (Salaün and Charpentier, 2001). In fact, the synthesis of glutamine is the major pathway for the assimilation of ammonium into organic matter, and asparagine represents the major receiver of the nitrogen of glutamine and a mobile reservoir for transport to growth sites (Joy, 1988). Arginine, on the other hand, is a precursor of the biosynthesis of polyamines and nitric oxide, which are involved in almost all physiological and biochemical processes as well as in plant growth and adaptation to stress (Yang and Gao, 2007).…”
Section: Electrophoretic Profile Of Date Palm Sapmentioning
confidence: 99%